The Social Aspects of Pension System Modernization in Modern Russia - BABAKAEV, Sergei V.; KAUROVA, Olga V.; KULYAMINA, Olga S.; MALOLETKO, Alexandr N.; VINOGRADOVA, Marina V. (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
This paper is aimed at revealing the social aspects of pension system modernization, associated with the need to identify and address the real social base of reforms, determine their level of social support, willingness of the population to accept and implement the proposed solutions to the problems of pension provision. The main research method of this problem is a sociological survey of the working population of Russia, which allows revealing the social conditions and the factors promoting or impeding the reform of the pension system. The article presents the main approaches to the modernization of the pension system in the context of studying social positions of employees of the leading Russian enterprises regarding different ways of the development of system of non-state pension provision (NSPPs). The authors describe the most popular forms of workers participation in corporate pension plans and justify the existing prospects of modernization of the pension system towards further development of NSPPs.